A laboratory model of post-Newtonian gravity with high power lasers and 4th generation light sources. (9th March 2016) - Gregori, G; Levy, M C; Wadud, M A; Crowley, B J B; Bingham, R
Abstract: Using the post-Newtonian formalism of gravity, we attempt to calculate the x-ray Thomson scattering cross section of electrons that are accelerated in the field of a high intensity optical laser. We show that our results are consistent with previous calculations, suggesting that the combination of high power laser and 4th generation light sources may become a powerful platform to test models exploring high order corrections to the Newtonian gravity.